Cineclubismo: towards literacy in cinema in educational spaces - Silva Arias, Catalina (Rastros Rostros, 2021)
This document presents an experience of pedagogical intervention through the cinema - club "Cineurosis" of the Department of Humanities, which shows the integration of cinema into academic spaces as a way to promote culture and educate students about the reception of audiovisual messages. The programmed activities are developed at the Cooperative University of Colombia (UCC, Barrancabermeja headquarters) for a diverse audience. Thus, the project focuses on creating a series of didactic resources for the inclusion of cinema in the specialized classroom and making the academic experience an aesthetic experience, which allows the encounter with Others, knowledge, audiovisual language and reflection. This process allowed for a pedagogical reflection based on specialized classrooms, the use of technology and audiovisual material as relevant elements in the development of Humanities classes and the creation of an extracurricular and transversal schedule focused on the approach of young people to cultural content, university life and the good use of free time.
Keywords: film club; cinema-forum; audiovisual material; critical thinking; film appreciation; cultural space